NATENG KEBUN KOPI DALAM HUKUM EKONOMI SYARIAH: NATENG KEBUN KOPI DALAM HUKUM EKONOMI SYARIAH - Yogi, Yogi; Hidayat, Fatah; Zuraidah, Zuraidah (Al-muamalah, 2023)
This thesis is entitled "A Juridical Review of Nateng Coffee Plantations in Sharia Economic Law in Muara Semah Village, Muara Pinang District, Empat Lawang Regency", with the background of the problem of the customary custom of the people of Muara Semah Village is that they often pawn their gardens for urgent needs but in Most of the pawns carried out by the local community do not have a time period for repayment so that the pawn recipient can take advantage of the garden produce pawned by the community. In this study, there are two things that are the focus of the author's study. First, how is the Nateng (pawn) mechanism for coffee plantations in Muara Semah Village. Second, how about the juridical review and settlement of sharia economic law regarding the Nateng mechanism for coffee plantations in Muara Semah Village. The research method is field research and this research method uses qualitative data based on primary data and secondary data. The primary data in this study are the results of interviews, observations, and direct documentation of objects related to research. As for the secondary data used in this study in the form of primary books which are considered representative of the research results as a complement to the primary data. From the results of the research conducted, it can be concluded that the system used in Nateng coffee plantations in Muara Semah Village is a system obtained from their ancestors, where Nateng does not have a maturity date provided that every year the yield from the coffee plantation harvest is divided into two and the coffee plantation can be returned when the pawnbroker has paid off all of his debts. The implementation of Nateng in Muara Semah Village is not in accordance with Islamic religious teachings because Murtahin is exploiting it which is detrimental to Rahin because Murtahin asks for half of the harvest from the coffee plantation without financial or manpower assistance from Murtahin and the money lent is not in accordance with the size the garden. The results of this study are expected to be useful for adding insight related to the science of sharia economic law, and are also expected to be able to contribute an understanding regarding problems that often occur, especially in the people of Muara Semah Village so that they can understand scientific matters related to pawning in Islamic Economic Law. Keywords: Nateng (Pawn), Coffee Plantation, Sharia Economic Law